Thermokinetics Synergistic Effects on Co-Pyrolysis of Coal and Rice Husk Blends for Bioenergy Production - Maham Tauseef (00000321016); Dr Abeera Ayaz Ansari (USPCAS-E, NUST, Islamabad, 2022)
TH-360
Keywords: MS-ESE Thesis MS Thesis